Odvisnost velikosti prevodnih elementov doba (Quercus robur L.) od temperatur na dveh rastiščih Querco-Carpinetum v Sloveniji - Jevšenak, Jernej (Acta silvae et ligni, 2015)
The aim of our study is to fully investigate the relationship between mean monthly temperatures and vessel features. Two vital and one declining groups of pedunculate oak from two Querco-Carpinetum sites in Slovenia are analyzed. Chronologies of mean vessel area and sum of vessel area were developed after previous high quality surface preparation and image analysis with macro EWVA in the ImageJ program. Declining group from Cigonca had the biggest average vessel and the largest amount of conductive tissue, which was linked to the dieback of this group. The analysis of temporal stability of correlation coefficients for declining group explained negative correlations, which were not stable in time. All groups were most responsive to the April temperatures. For all groups, climate signal was the strongest in the mean vessel area parameter. For vital group from Mlače we can expect, in the event of continuous rising of mean temperatures, bigger mean vessels that are more likely to be affected by cavitation. Lower ground water table in 1982 at Cigonca coincides with the reduced climate signal in the vessels.
Keywords: dendroekologija; propadanje hrastov; anatomija lesa; okoljski signal; Quercus robur; traheje ranega lesa